"A Sigh of Sympathy": Thomas Hardy's Paralinguistic Aesthetics and Evolutionary Sympathy. Issue 1 (2022) - Spence, Rebecca
Abstract : This essay turns on a quiet, though intriguing, expression—the sigh—and considers the aesthetic work that it performs in the novels of Thomas Hardy. While the primary focus of the essay is the aesthetic, communicative, and biological functions of the sigh itself, the broader imperative is to demonstrate how paralanguage was implicated in broader nineteenth-century debates about evolution. It does this by setting Hardy's sighs in conversation with Herbert Spencer's essay "The Origin and Function of Music" (1857). Hardy's writing dramatizes a comparable associative relationship between paralanguage, listening, and sympathy to that which Spencer proposed in "The Origin" but does not replicate the ideological conditions of Spencer's model, which had reserved the highest forms of sympathy for the "cultivated" few. Hardy's aesthetic interest in the sigh, I argue, is more overtly related to how the biosemiotics of paralanguage communicate insights into emotional conditions that are outside the grasp of language.